Influence of Short-term Maize–Green Manure Cover Crop Rotations on Germinable Weed Seed Bank under Conservation Agriculture - Tatenda, Rugare Joyful; Jacobus, Pieterse Petrus; Stanford, Mabasa (Asian Journal of Agriculture and Rural Development, 2021)
The effects of one- and two-year maize-cover crop rotations on weed seed bank density and species composition were evaluated in fields at the University of Zimbabwe (UZ) and the International Maize and Wheat Improvement Center (CIMMYT, Harare) between 2014 and 2017. Nine cover crops were rotated, and maize and weed seed bank analyses were done using the seedling emergence method. Maize was used as the control. The results indicated that weed seed density was not significantly (p > 0.05) affected by cover crop mulch type across the seasons. There was a significant (p < 0.05) decline in weed density in the second maize phase of the rotation in UZ Field A. Bidens pilosa, Galinsoga parviflora, Amaranthus hybridus and Eleusine indica were the dominant weeds. B. pilosa density significantly decreased in the second season in UZ Field A but did not vary significantly among cover crops. Significant changes in weed species richness, evenness, and diversity were observed only in the second phase of the rotation in UZ Field A. The results suggest that maize-cover crop rotations could be effective in reducing seed bank size in the short term but have no short-term effect on weed species community composition.